Obstacles to public elementary libraries development as learning resources in Singaraja City - Luh Putu Sri Ariyani; Anak Agung Ngurah Anom Kumbara; Nengah Bawa Atmadja; Ida Bagus Gde Pujaastawa (Jurnal Kajian Informasi dan Perpustakaan, 2022)
The library is an essential learning resource center for schools. For this reason, every school or madrasa is required to have a library that meets national education standards. Although formal provisions require educational institutions to have a library, many schools do not yet have a library. The development of school libraries, especially elementary schools (SD), is still lacking compared to the middle school, high school, and college libraries, thus giving the impression that SD libraries are marginalized. This study explored the development constraints that led to the marginalization of elementary school libraries in Singaraja, Bali. This research used a qualitative approach in the form of multiple case studies. The data collection techniques were in-depth interviews with appointed informants, total and purposive samples, and snowball sampling. Data analysis in this study followed Peter Berger's model with conceptualization, proof, and objectivation steps. The results indicated that there were several obstacles to the development of elementary school libraries, namely (1) the dadi-dadi dogen ideology adopted by the principal; (2) the teaching and learning process is still teacher-centered; (3) a comprehensive education system; (4) unprofessional librarian; (5) the government is not in favor of the school library management policy; and (6) free school jargon. These findings prove that the general assumption about the constraints on developing school libraries due to limited financial capital is not entirely true. There are other more important factors, namely power relations related to ideology.